Cost per response analysis of repository corticotropin injection versus other alternative treatments for acute exacerbations of multiple sclerosis - George J Wan; Ishveen Chopra; John Niewoehner; Samuel F Hunter (BioExcel Publishing Ltd, 2020)
Background: Relapses are common in patients with multiple sclerosis (MS) even after the use of disease-modifying therapies. Repository corticotropin injection (RCI), plasmapheresis (PMP), and intravenous immunoglobulin (IVIg) may be utilized as alternative therapies in the management of MS relapse. There is a lack of health economic studies on these alternative therapies for the acute exacerbations of MS. The objective of this study was to estimate the cost per response of RCI compared with PMP or IVIg from the United States (US) commercial payer perspective. Methods: Costs and response rates were sourced from published peer-reviewed observational studies. The cost of care included MS-related inpatient, outpatient, and medication costs. Treatment response was defined as no evidence of additional relapse treatment or procedure claims within 30 days after treatment. The cost per response for each treatment was calculated by dividing the total annual cost of care by the proportion of patients with resolved relapse for each treatment. The incremental cost per response ratio was calculated by dividing the difference in costs and the proportion of responses for RCI versus PMP or IVIg. One-way sensitivity analysis (OWSA) was conducted for both costs and response rates. All included costs were inflated to the 2019 US dollars. Results: With a lower total annual cost of care and a higher response rate, RCI had a lower cost per response (US$141,970) compared with PMP or IVIg (US$253,331). RCI had a lower cost per response even when more stringent estimates for RCI were applied in the OWSA. The annual cost of care had a greater influence on the cost per response in the OWSA. Conclusions: Based on the estimates from the real-world evidence, our economic evaluation suggests that RCI may have real-world clinical and economic benefits for patients with MS relapse who fail on corticosteroid therapy.